Effect of Hematocrit on Wall Shear Stress for Blood Flow through Tapered Artery. Issue 2 (11th February 2014) - Singh, A. K.; Singh, D. P.
Abstract : The purpose of this study to show the effects of Hematocrit (Red blood cells), height of stenosis, porous parameter and velocity of blood on wall shear stress of the flow of blood through tapered artery. The study reveals that wall shear stress reduces for increasing Hematocrit percentage. It is also observed that wall shear stress increases as stenosis height and porous parameter increase whereas it decreases with the increasing values of velocity of blood and slope of tapered artery.